Aproximação entre atividades narrativas: o cinema e a história - Queiroz , Filipe Artur de Sousa (2016)
This work has as it main objetive to discuss the historical narrative. The strategy to do it is the approach between cinema and history. The central purpose is about this contract is the one simple question: in the logicality and specifically film narration definition are useful to the reflexion about the historical narrative type? The way I found to make this approach is by the films Quentin Tarantino reflective analysis. In this occasion I try to work with specific cut-outs theatrical about the Gaudreault and Jost narratology, and the André Parente philosophy. And to the history theoretical support I use the history theory of Jörn Rüsen and philosophy of Frank Ankersmit language.